EFEKTIVITAS KINERJA GURU TERHADAP MOTIVASI BELAJAR SISWA - Nimim Ali (Universitas Negeri Gorontalo, 2021)
Improving the quality of learning requires the performance of a teacher. This study aims to: (a) How is the performance of teachers in MTs. Sullamul Falah Tombos. (b) How is the performance of teachers in improving students’ motivation. This study used a phenomenological approach with qualitative research. Data collection techniques were carried out through: observation, interviews and documentation. Using purposive sampling technique. While the validity of the data used triangulation techniques. The results showed that in general the performance of teachers at MTs Sullamul Falah Tombos was quite good, in terms of reflecting on their duties as a teacher and as an administrator who organizes quality learning activities through planning, implementing and assessing the teaching and learning process whose intensity is based on work ethic, and high professional discipline. Students learning motivation is good where the achievement of student learning outcomes competencies on average reaches a value of 7 and a value of 8 for each subject taught by the teacher. Attention is needed by a teacher to influence student learning motivation.